Analisis Fundamental Makro, Karakteristik Perusahaan Terhadap Kinerja Perusahaan dengan Struktur Modal, Struktur Kepemilikan, dan Opini Audit sebagai Variabel Intervening pada Perusahaan Tekstil dan Garmen - Sari, Nur Fitroten Dian; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the relationship between macro fundamental analysis, company characteristics, and company performance with capital structure, ownership structure, and audit opinion as intervening variables in textile and garment companies. The textile and garment industry faces various challenges such as global competition, fluctuations in raw material prices, and changing consumer preferences. Industry and company analysis is important to understand the company's performance. Factors such as company size, leverage, and profitability can affect a company's performance. The ownership and capital structure also plays an important role. Audit opinions can improve investor confidence and company performance. This research can help textile and garment companies make better decisions to improve their performance. This study examines the relationship between macro fundamental variables, company characteristics, ownership structure, audit opinion, and company performance. The results showed that only three of the eleven hypotheses proposed were accepted, with the finding that the characteristics of the company had a significant influence on the company's performance. This research was conducted using a quantitative method using secondary data from textile and garment companies on the Indonesia Stock Exchange for the 2018-2022 period. Testing shows that the Ownership Structure has a significant influence on the company's performance, while the Capital Structure has no significant influence. This study supports previous findings and rejects other different studies. The references used in this study cover a wide range of topics related to corporate finance and management.